Metabolites in the milk of buffalo, Holstein cross, indigenous and Red Chittagong cattle of Bangladesh - Islam, MA; Uddin, ME; Jahan, R; Wadud, A; Sarkar, MM (Bangladesh Journal of Animal Science, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Low molecular weight chemical compounds or intermediate products of a metabolism or other cellular processes are called metabolites. The objective of the present study was to investigate the variations in the metabolite concentration in the milk from crossbred water Buffalo (B), Holstein cross (H), Indigenous cattle (I) and Red Chittagong Cattle (R) and the relationships among those metabolites.<span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-GB"> T<span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">he concentration of citric acid, ? -keto glutaric acid (?-keto GA), orotic acid, pyruvic acid, succinic acid, lactic acid, formic acid, uric acid and propionic acid were measured by using High Performance Liquid Chromatography. Pooled milk samples of nine B, fifteen I and twenty R cows were collected from the research farm of Bangladesh Livestock Research Institute, Savar, Dhaka, Bangladesh. The pooled milk samples of H were collected from twenty five cows of <span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-GB">Central Cattle Breeding Station and Dairy Farm<span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-GB">, Savar, Dhaka, Bangladesh. All the sampling was done from the morning milking. The samples were preserved by adding bronopol tablet and frozen and stored at -20 °C.<span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Except propionic acid, all the metabolites varied significantly (p<0.01) among the milk types and B milk had lowest concentration of them. The highest concentration of citric acid (ppm) was 2245.50±39.90 in I milk followed by 2156.60±26.60 in R, 1858.30±8.70 in H and 1366.70±33.70 in B milk. The H, I and R milk were found similar in their ?-keto GA content. Similarities were also found for succinic acid between H and R milk and so for H and I milk in uric acid content. Highest formic acid was found in H milk (392.78±2.23 ppm) and the lowest was 308.91±3.75 ppm in R milk while B and I milk was found similar. The lowest concentration of uric acid was found 0.44±0.26 ppm in B milk and R milk had the highest content (11.38±1.10 ppm). Pyruvic, formic and propionic acids showed no significant relationship among them and with others as well. The most highly significant (p<0.01) correlation was found between orotic and ?-keto GA (r=0.915) and between uric and succinic acid (r=0.914). So, the metabolites showed a considerable variation in their concentration in different types of milk and also some of the parameters showed significant relationship among them. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18504 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2): 152-157 <span style="font-size: 8.5pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->